1998
DOI: 10.1097/00002030-199817000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Presence of the variant mannose-binding lectin alleles associated with slower progression to AIDS

Abstract: Indications for a weak pre-AIDS protective effect of variant MBL alleles were demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 21 publications
0
27
2
Order By: Relevance
“…This is further supported by the finding that HIV-1-infected men with variant MBL alleles (95% of whom were heterozygote) progressed more slowly to AIDS and death. 26 We previously reported that the variant MBL alleles, mainly in the heterozygous state, are prevalent in patients with sickle cell anemia who had not suffered severe infections. 27 Similarly, other studies have demonstrated that heterozygotes are protected against tuberculosis infection.…”
Section: Mbl Genotypes and Infectionsmentioning
confidence: 98%
“…This is further supported by the finding that HIV-1-infected men with variant MBL alleles (95% of whom were heterozygote) progressed more slowly to AIDS and death. 26 We previously reported that the variant MBL alleles, mainly in the heterozygous state, are prevalent in patients with sickle cell anemia who had not suffered severe infections. 27 Similarly, other studies have demonstrated that heterozygotes are protected against tuberculosis infection.…”
Section: Mbl Genotypes and Infectionsmentioning
confidence: 98%
“…Elevated MBL serum levels correlate with better survival in patients with AIDS and homozygosity for MBL variant alleles B, C and D have been associated with lower MBL serum levels and an increased susceptibility to HIV-1 infection Piacentini et al, 2009). Studies that have looked at the effects of MBL genotype on the clinical outcome of HIV-1 infection in therapy-naïve subjects were unable to make a definitive correlation between MBL genotype (homozygous versus WT for MBL variants) and HIV-1 disease non-progression Maas et al, 1998). For instance, in a cohort study of HIV-infected homosexual seroconverters (n596) who were followed for 10 years, the correlation between MBL genotype and the time to AIDS was not statistically significant (P50.8).…”
Section: Innate Immunitymentioning
confidence: 99%
“…Tel. : +98 411 3357126, Fax: +98 411 3364666. acetylglucosamine and activates the complement system independently of antibodies via two associated serin protease, mannose binding lectin-associated serine protease 1 and 2 (Jack et al, 2001;Mass et al, 1998;Thiel et al, 1997). C1q and mannose binding lectin, as well as lung surfactant protein A, share the same phagocytic receptor, which is present on a variety of cells, including phagocytes, platelets, and endothelial cells (Nepomuceno et al, 1999;Nepomuceno et al, 1998).…”
Section: Introductionmentioning
confidence: 99%